Η λειτουργία της «εν Θεσσαλονίκη Δημοτικής Σχολής Κουφαλιωτών (1907/1908-1913/1914) - Βαχάρογλου, Ευστράτιος Θ. (Μακεδονικά, 2011)
The aim of this paper is to bring to light the organization and the operation of Koufalian’s Primary School in Thessaloniki at the beginning of the20th century. The operation of the Institution was important because it wasbased on the initiative of a group of people from Koufalia, a region next toThessaloniki.The operation of this School elects the metropolitan and educational roleof Thessaloniki and its help in residents, which were forced to leave fromregions, because of bad social and political circumstances, which impendedthe operation of Greek schools mainly in Macedonia.There are no bibliographic reports for this School and the sources arevery few. We can characterize the operation of the School «autonomous» as itwas not included initially in the network of Community schools.More specifically, this paper examines the following issues: a) The aim and goals of School’s functioning.b) The financial support of the Institution, the teaching personnel.c) The number of the pupils, the age limit for attending classes, thetime of enrolling, the pupil’s place of origin, their social and financialstatus.